Conformity Analysis of Online Teaching Materials Content and Curriculum on the Ministry of Education and Culture Website to Support the Distance Learning - Anjas Rusdiyanto Soleh; Eko Purnomo; Dini Restiyanti Pratiwi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to identify the suitability of the content of the teaching materials contained in the old sumber.belajar.kemdikbud.go.id with the coverage of the material contained in the curriculum, especially in the core competencies and basic competences of Indonesian subjects. This research uses qualitative research by applying descriptive methods. Data collection used in this research is to use observation, note-taking, and documentation techniques. Data analysis in this study used content analysis techniques. The results in this study indicate that the content of teaching materials with the curriculum contained in the sumber.belajar.kemdikbud.go.id, especially in Indonesian subjects, is in a fairly appropriate category. This can be seen from the material presented that is quite a lot in accordance with the scope of material contained in the core competencies and basic competences of Indonesian subjects in the curriculum, in addition there are several material presentations that are not in accordance with the coverage of core competencies and basic competencies. Indonesian subjects in the curriculum.